Modulation of cell wall synthesis and susceptibility to vancomycin by the two-component system AirSR in Staphylococcus aureus NCTC8325 - Sun, Haipeng (BioMed Central, 2013)
BACKGROUND: Vancomycin has been the medication of last resort to cure infections caused by Staphylococcus aureus since the increase in the prevalence of methicillin-resistant Staphylococcus aureus (MRSA). Some strains have developed vancomycin-intermediate resistance, which is generally associated with altered expression of or mutations in some part of the two-component system (TCS), such as GraSR, VraSR, and WalKR. RESULTS: We deleted the AirSR TCS in S. aureus NCTC8325 and compared the resultant transcript levels with those of its parent strain using microarray analysis. The results indicated that more than 20 genes that are related to cell wall metabolism were down-regulated in the airSR mutant. The airSR mutant exhibited reduced autolysis rates and reduced viability in the presence of vancomycin. Real-time reverse transcription PCR and DNA mobility shift assays verified that AirR can directly bind to and regulate genes that function in cell wall metabolism (cap, pbp1, and ddl) and autolysis (lytM). CONCLUSIONS: AirSR acts as a positive regulator in cell wall biosynthesis and turnover in Staphylococcus aureus NCTC8325.